Consumption of alcoholic beverages and practice of binge drinking among hairdressers - Fernanda Matos Fernandes Castelo Branco; Germana Teixeira de Sousa; Nathanni Queiroz dos Santos Marques; Ariane Aparecida Santos Moraes; Fabio Rodrigues Trindade; Tancredo Castelo Branco Neto; Carlos Manuel Dutok-Sánchez (Universidade Federal do Ceará, 2021)
Objective: to verify the consumption of alcoholic beverages and the practice of binge drinking among hairdressers. Methods: cross-sectional study conducted with 51 beauty salon professionals. We used a questionnaire with socio-demographic characteristics and about the practices of consumption of alcoholic beverages. For the identification of the use in binge drinking, the key question was guided. Descriptive and inferential statistical analysis was performed. Results: 84.3% were alcohol consumers, 51.0% had between one and ten years of consumption and 72.5% consumed beer. In relation to the use in binging, 37.3% of the sample made occasional use of risk, at least once a month. The highest rates of binge drinking were related to male gender, single and young and the evangelical religion was associated with a lower or no consumption of alcoholic beverages. Conclusion: the data pointed to alcohol consumption and frequent binge use related to likely alcohol dependence.